Educational Reforms Amid COVID-19 in Thailand - Poungjinda, Wachiraporn; Pathak, Shubham (Frontiers in Education, 2022)
Education is essential for any country to secure its future, but COVID-19 has caused considerable difficulty in Thailand. The COVID-19 pandemic harms the education of the students. The online education system is adopted in almost all parts of the globe. However, the pandemic has been impacting the overall quality of the education system. This research explored the experiences of law students in Thailand by analyzing several factors which affect their intellect. The methodology adopted for this study was a multiple method study. The sample size of 330 law students selected from leading Thai universities was analyzed qualitatively through Strength, Weakness, Opportunity, and Threat (SWOT) analysis and regression model for the quantitative analysis. The findings revealed that factors including internet availability, accessibility to own gadgets, online resources, government, social media, and classrooms have a significant impact on the education system of Thai law students. The study paves way for further microanalysis of the educational system in Thailand with the perceptions and experiences of teachers and parents.